Literature Study: The Effectiveness of Role-Playing Model in Social Studies Learning at Elementary School - Utami, Nanda Dwi; Kurnianti, Endang M; Winarni, Susi (International Journal Education and Computer Studies (IJECS), 2025)
The learning in the Social Studies Programme aims to give students the knowledge and skills to function in their life with issues concerning their family, community and nation. But social study learning is also known to be a dull curriculum which involved memorisation with relatively little student involved. It is why role-playing models in the learning of social studies are among the desired solutions in order to make meaningful learning and easy to understand. This study sought to explore role-play models in the social studies teaching and process and student out come. The approach adopted in this paper was a literature review conducted on 11 articles retrieved from Google Scholar published in the last five years. From the literature review, the Role-Playing Model is proposed as an interesting and creative learning strategy to increase the quality of learning social studies, especially at elementary school